Йакут: первоисточники некоторых сведений о Хазарии и Хазарском море - Калинина, Т.М. (Хазарский альманах, 2015)
Статья посвящена теоретическим выкладкам арабского автора Йакута о местонахождении области Хазар на Земле и ряду реальных известий о море Хазар. Первоисточником построений Йакута была информация алБируни; конкретные сообщения о море Хазар были тесно связаны с материалами Ибн Фадлана, ал-Истахри, ал-Бируни. В книге Йакута имеются и другие данные, которые необходимо анализировать в будущем. The article is devoted to some theoretical information of Arab author Yakut about the location of the Khazar region on Earth and the real datas about the Khazar’s Sea. The primary source of the materials of Yakut were the views of al-Biruni; concrete news about Khazar’s Sea the were associated with the massages of Ibn Fadlan, al-Istakhri, al-Biruni. There are also other data about Khazars in Yakut‘s book which need to be analyzed in the future.